The role of AI and ML in advancing electronically controlled drug delivery systems - Bappaditya Chatterjee (Journal of Applied Pharmaceutical Science, 2025)
No abstract is available.
Keywords: Artificial Intelligence, Machine Learning, open-loop system, drug delivery systems